PENINGKATAN HASIL BELAJAR SISWA TENTANG MEMBEDAKAN ZAT TUNGGAL DAN CAMPURAN MELALUI MODEL STUDENT TEAM ACHIEVEMNT DIVISION KELAS IV SD KUPANG - Adoe, Treesly Y.N (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to improve student learning outcomes in class V science subjects through the application of the STAD learning model. The research method used is Classroom Action Research (CAR) or Classroom Action Research (PTK) using the STAD learning model which is carried out in 2 cycles. One cycle consists of four stages, namely: planning, implementation, observation and reflection. This research was conducted at SDI Fatufeto 1 Kupang City. The research subjects were class V students of SDI Fatufeto 1 Kupang City for the 2022/2023 academic year, consisting of 24 students. The action taken is to apply the STAD learning model. Data collection techniques include observation, tests and documentation. The results of this research show that learning on theme 9 subtheme 1 learning 2 using the STAD learning model can improve the learning outcomes of SDI Fatufeto 1 class students in Kupang City. In cycle I, the criteria were Poor (K) with a percentage of completeness of student learning outcomes obtained at 37.5%, while student learning outcomes in cycle II received good criteria (B) with a percentage of completeness obtained at 95.84%. Meanwhile, data from student observations in cycle I, students obtained a total score of 955.50 with an average score of 72.50 and received adequate criteria (C), while in cycle II the student activity score increased to 1,142.50 with an average score 88.75 and received very good criteria (SB).